Risk factors for postoperative vocal fold fibrosis following microlaryngeal surgery - Po‐Hsuan Wu; Chi‐Te Wang (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Objective To analyze the risk factors for postoperative vocal fold fibrosis (PVF) in patients undergoing microlaryngeal surgery (MLS) for benign vocal fold lesions. Study Design Retrospective study. Methods We retrospectively included patients who had undergone MLS for vocal polyps, nodules, mucus retention cysts, fibrous mass, or Reinke's edema. Data on the patients' clinicodemographic characteristics and intraoperative findings were obtained by reviewing their clinical records. PVF was defined by the presence of an adynamic segment of membranous vocal folds or a marked reduction in mucosal wave amplitude on post‐MLS (6 weeks) videolaryngostroboscopy. The risk factors for PVF were analyzed through univariate and multivariate logistic regressions. Results This study included 89 patients, of whom 16 (18%) were given a diagnosis of PVF. A significantly increased incidence of PVF was noted in patients with fibrous mass (p < .01). The univariate analysis indicated that lesion attachment to the vocal ligament, prolonged surgical duration (>60 min), and symptom duration (>12 months) were significantly correlated with PVF (p < .05). The multivariate analysis confirmed that diagnosis of fibrous masses, lesion attachment to the vocal ligament and symptom duration are significant risk factors for PVF. Conclusion PVF is more common in patients with fibrous masses. Lesions attachment to the vocal ligament and prolonged symptom duration appear to be other significant risk factors for PVF. Level of Evidence 4